PELATIHAN KONSELING MULTIBUDAYA DALAM PENDIDIKAN KONSELOR - Moh.Yanuar Akmal Alfaresi; Sayidah Sa’idah; Raisya Presiri; Dinda Meita Sari; Zulia Dewi; Ari Khusumadewi (Jurnal Mahasiswa BK An-Nur : Berbeda, Bermakna, Mulia, 2026)
This paper discusses the importance of multicultural counseling training for counselors, emphasizing the need for professional development to enhance counselors' competencies in dealing with diverse cultural backgrounds. In a multicultural society like Indonesia, where cultural, ethnic, religious, and linguistic diversities prevail, counselors must possess the ability to understand and respect these differences to provide relevant and inclusive services. This paper outlines the stages of multicultural counseling training, from increasing cultural awareness to direct involvement in multicultural counseling practices. The training also involves various techniques such as personal experiences, direct experiences, workshops, and cultural assimilators. Furthermore, the paper emphasizes the necessity of evaluating the effectiveness of this training to ensure it meets its goals. The findings indicate that such training is essential in improving the counselors' ability to deliver fair and effective counseling interventions, fostering an inclusive and adaptive approach to multicultural challenges.